Case Report: Chicken bone-induced perforation of duodenal diverticulum in the third portion successfully treated by endoscopy - Zhou, Hui-hui; Ma, Cui-mei; Wang, Yan; Zhang, Yao-wen (Frontiers in Medicine, 2025)
Duodenal diverticulum (DD) perforation is a rare but severe clinical emergency with a reported mortality rate as high as 30%. DD most commonly occurs in the second portion of the duodenum (D2), particularly in the periampullary region, accounting for 78.3% of cases. In contrast, diverticula in the third portion of the duodenum (D3) are relatively rare. Traditional treatment methods include conservative therapy, percutaneous drainage, and surgical intervention. However, with advancements in gastrointestinal endoscopy, endoscopic treatment has emerged as a viable option. A 71-year-old male patient presented with upper abdominal pain. Laboratory tests revealed elevated white blood cell count and C-reactive protein levels. Abdominal CT showed a perforated diverticulum in D3 with a suspected foreign body. After 5 days of conservative treatment with no improvement, endoscopic intervention was performed. Using a gastroscope equipped with a transparent cap, foreign body forceps, the embedded chicken bone and surrounding debris were removed, and the fistula was closed with metallic clips. Follow-up CT scans showed significant improvement, with no recurrence of symptoms at 18 months. The successful endoscopic treatment of this D3 diverticulum perforation highlights the potential of endoscopic therapy in managing complex duodenal diseases. Compared to traditional surgery, endoscopic treatment offers minimal invasiveness, faster recovery, and fewer complications. This case expands the application of endoscopic techniques to D3 perforations, providing valuable experience for future similar cases.